Rancang Bangun Purwarupa Sistem Pendeteksi Kepadatan Lalu Lintas dengan Memanfaatkan Komunikasi Vehicle-To-Everything (V2x) untuk Kendaraan Cerdas - I Putu Gde Raditya Wikadhyana; Ngurah Indra ER; Widyadi Setiawan (VISA: Journal of Vision and Ideas, 2026)
Increased traffic density can increase the risk of traffic accidents, congestion and traffic disruption. This is due to the very high increase in the number of vehicles every year. For this reason, we need a technology that is able to provide a solution to overcome traffic congestion. Vehicle-to-Everything (V2X) is a general term that refers to communication technology between a vehicle and any entity that can affect or may be affected by the vehicle. The use of this communication can reduce traffic jams, and also provide efficiency and safety in driving. Therefore, in this research, a low-cost Vehicle-to-Everything (V2X) communication system was designed using components such as ESP32, NRF24L01 Wireless Modules, Ublox Neo M8N GPS, and OLED display. Tests were also carried out to determine the level of accuracy of the device both in stationary and moving conditions by paying attention to the test parameters of the traffic density detection system, such as average vehicle speed, vehicle queue length, and vehicle travel time to the RSU. In this study, it was found that the level of accuracy of the device based on test parameters compared with direct measurements and manual calculations was stated to be of good accuracy. So it is hoped that in the future we will be able to carry out developments to produce better traffic density detection devices that are ready for use by motorists.